Dynamic response of fixed offshore platforms to environmental loads - Azarhoushang, Azin (Curtin University, 2010)
In this thesis a simplified method for dynamic response of jacket type offshore structures to extreme environmental load is investigated using existing experience and the procedures available within the industry. Fixed Jacket type offshore platforms may, under extreme wave loading conditions, exhibit significant nonlinear behavior. This must be accounted for in the design of such platforms, in order to ensure satisfactory structural safety. The complicated and nonlinear dynamic platform behavior implies that a wide number of significant uncertainties are introduced to the design process through the included mathematical models, analysis methods and the practical use of these methods. The major sources of nonlinear behavior are the wave loading, the damping mechanisms and the soil structure interaction. The inclusion of nonlinear dynamic platform behavior in the design process implies that nonlinear stochastic dynamic response based on time domain simulation methods must be applied. Time domain stochastic dynamic response analysis is an analysis method which will be a central element of the procedure. However, it seems not to be clear so far how this method should be integrated in a practical design procedure. Initially an overview of the different sources of nonlinear platform behavior is clarified with the underlying mechanism. Furthermore, it is outlined how those nonlinear effects may be accounted for with a special focus on estimation of extreme response and dynamic amplification factors. The discussion and outlines are illustrated by an example of fixed offshore platform. Finally the practical use of the method in the design of fixed jacket type offshore platforms is recommended.